2005
DOI: 10.1080/02652030500307172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to chemical migrants from food contact materials: A probabilistic approach

Abstract: A two-dimensional probabilistic model has been developed to estimate the short-term dietary exposure of UK consumers to migrants from food packaging materials. The current EU approach uses a default scenario of assuming that all individuals are 60 kg weight and consume 1 kg of food packaged in the material of interest per day. Using four UK National Dietary and Nutrition Surveys comprising 4-7 day dietary records for different age groups and survey years, a sample representative of the UK population has been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…The consumption data include high consumers, the protection of whom has always been a priority for the EU, EFSA and industry. The surveys were either 4 or 7 days (for further details consult Holmes et al 1 ). The three surveys showed that 884 272 individual food items were consumed in total.…”
Section: Weight Of Each Food Item Consumedmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption data include high consumers, the protection of whom has always been a priority for the EU, EFSA and industry. The surveys were either 4 or 7 days (for further details consult Holmes et al 1 ). The three surveys showed that 884 272 individual food items were consumed in total.…”
Section: Weight Of Each Food Item Consumedmentioning
confidence: 99%
“…In earlier papers we have described the development of a two-dimensional probabilistic model to estimate the short-term dietary exposure to chemical migrants from food packaging materials 1 and the application of this model to estimate exposure to a generalized migrant from light metal packaging -principally food cans. 2 In the current work we have extended the application of the model to the specific question of the migration of bisphenol A diglycidyl ether (BADGE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008;Poças et al, 2009;Foster et al, 2010). Probabilistic approaches have been applied for coupling exposure assessment (Holmes et al, 2005) and migration modelling (Poças et al, 2010). According to a probabilistic study, changes in eating habits over time have a smaller impact on dietary exposure to migrants than changes in packaging usage, packaging composition and migration levels (Northing et al, 2009).…”
Section: General Introductionmentioning
confidence: 99%
“…One of the main issues is that the current method in the EU is viewed as being overly conservative and does not give any indication of the true or real exposure to a food packaging migrant. To refine the exposure assessment, progress has been made in relation to the use of probabilistic exposure assessment modeling to estimate exposure to a food packaging migrant (Holmes et al 2005). This methodology accounts for variability and uncertainty in the exposure assessment and provides a more realistic exposure based on available data and on expert opinion.…”
Section: Introductionmentioning
confidence: 99%